Overview of the Main Types of Contact Lenses for Aphakic Children Under 5 - Corbeil, Marie-Eve; Ganivet, Amélie; Michaud, Langis (Canadian Journal of Optometry, 2014)
Contact lenses are often the first choice for visual correction of aphakic children. There are several types of lens that can successfully be fitted to correct ametropia, stimulate visual selecting, and maintain ocular health. Several factors are important for choosing the type of lens. Usually, the first lens fitted is made of silicone (Elasofilcon A, Bausch & Lomb, Rochester, Ny) with an evolution to a custom silicone hydrogel lens over time. Although fitting in young aphakic children presents many challenges, contact lenses often remain the best option for the correction of refractive errors after congenital cataract surgery. An overview of the main types of contact lens available for aphakic children and their characteristics are presented.